Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau Dari Gaya Belajar Pada Materi Spltv Kelas X SMA Karya Sekadau - Aurelia Ica; Iwit Prihatin; Hartono , Hartono (Lembaga Pengembangan Kinerja Dosen, 2022)
The research method used in this research is descriptive qualitative research and the form of research used is a case study with the subject being students of class X IIS 4 consisting of 30 students. The data collection tool used was a learning style questionnaire, a test of mathematical problem solving abilities in the form of 2 essays, and interviews with 6 students, namely 2 students with a visual learning style, 2 students with an auditory learning style, and 2 students with a kinesthetic learning style. Before being used in this study, the questions were tried out to determine validity, discriminatory power, index of difficulty, and test reliability. From the results of the study it can be concluded that the students' mathematical problem-solving abilities in terms of learning styles in SPLTV material as a whole have a percentage of 65% with moderate criteria. The sub-problems in this study are as follows: (1) The mathematical problem solving ability of students with a visual learning style has a percentage of 64.82% with moderate criteria; (2) Mathematical problem solving ability of students with auditory learning style ability has a percentage of 72.92% with moderate criteria; (3) The ability of students' mathematical problem solving with learning styles has a percentage of 61.72% with low criteria.